Conceito de meio ambiente no direito brasileiro a partir da lei n.° 6.938/81: do reducionismo legal e constitucional ao conceito jurídico complexo - Araujo, Alana Ramos (2019)
The thesis is situated in the field of environmental law. It object is to study the legal concept of the environment. This object was investigated in the Brazilian legal context based on the conceptualization set forth in Law No. 6.938/81, which deals with the National Environmental Policy (PNMA), passing through the constitutional concept of the Constitution of the Federative Republic of Brazil of 1988 (CF/88) and by the doctrinal concept, which consists of the concept elaborated by jurists in the area of environmental law and who are a reference as a material source of Brazilian environmental law. In PNMA, the concept of environment is defined from its natural aspect; in CF / 88, the concept of environment is defined from its human aspect; the environmental juridical doctrine defines it from a four dimensional concept in which the environment is the set of natural, artificial/constructed, cultural and work elements. In spite of such a polysemic conception, the doctrine points out the necessity of filling the content of the concept of the environment in concrete cases through judicial interpretation, admitting that, even with the parameters of PNMA, CF/88 and doctrinal construction, environment is an undetermined legal concept. This understanding reveals the difficulty of delimiting the legal concept of the environment. Thus, the thesis starts from the problem of how the Brazilian legal system conceptualizes the environment from the PNMA to the present time through its normative programs, particularly, through the jurisprudence. Based on this problem, the purpose of the thesis was to characterize the legal concept of the environment and propose a new conceptualization in the Brazilian legal organization4. This objective was achieved through the analysis of CF/88, the Constitutions of the 26 Member States of the Brazilian Federation and the Organic Law of the Federal District; at the legal level, I analyzed PNMA, the Environmental Policies of the 26 Member States and the Federal District. Regarding the second order observation, I5 analyzed the judgments of the Superior Court of Justice (STJ) and the 5 (five) Federal Regional Courts (TRFs). These normative programs, with regard to the conceptualization of each one about the environment, were analyzed through three theoretical pillars: complex thinking (MORIN, 2005a), environmental rationality (LEFF, 2006) and social systems theory LUHMANN, 2002a). Through this theoretical framework, I assumed that we are situated in a context of environmental crisis, of the insufficiencies of modern science to deal with the complexity of modernity and the lack of rationality of the law to internalize environmental values in legal theory and technique. The normative programs analyzed were treated using MAXQDA software that allowed a quantitative and qualitative methodology, revealing that the Brazilian courts' conceptualization parameter is the constitutional concept of article 225 of CF/88, reinforcing: the anthropocentric character of the concept of the environment; the operational closure of the law in relation to other non-legal environmental grounds; the non-internalization of environmental values in law; the reductionism of the concept of environment in the Brazilian legal system. The research brings as general confirmation the need for a new concept of environment in the Brazilian legal system, new foundations and a complex methodology to guide law in the ways of environmental justice.